Comparison of the mitral valve morphologies of Cavalier King Charles Spaniels and dogs of other breeds using 3D transthoracic echocardiography. (20th September 2018) - Menciotti, Giulio; Borgarelli, Michele; Aherne, Michael; Camacho, Paula; Häggström, Jens; Ljungvall, Ingrid; Lahmers, Sunshine M.; Abbott, Jonathan A.
Abstract : Background: Myxomatous mitral valve disease (MMVD) is more prevalent in Cavalier King Charles Spaniels (CKCSs) compared to dogs of other breeds at a given age. Abnormal valvular stress is thought to contribute to the development and progression of MMVD, and a relationship exists between mitral valve (MV) morphology and stress acting on the valve. Objectives: To determine whether the MV morphology of healthy adult CKCSs differs from the morphology of healthy adult dogs of other breeds determined by RT‐3DTTE. Animals: Thirty‐five healthy CKCSs and 41 healthy dogs of other breeds. Methods: Prospective cross‐sectional study. Dogs underwent physical examination, conventional echocardiography, and RT‐3DTTE. RT–3DTTE datasets were analyzed using dedicated software for MV morphologic analysis. Morphologic variables were compared between CKCSs and dogs of other breeds. Results: The MV of healthy CKCSs had a smaller annulus height (0.46 ± 0.11 vs. 0.56 ± 0.17; P = .0021), tenting height (0.26 ± 0.12 vs. 0.42 ± 0.18; P < .001), tenting area (0.42 ± 0.15 vs. 0.79 ± 0.34; P < .001), normalized tenting volume (0.09 [0.05–0.13] vs. 0.14 [0.10–0.20]; P < .001), and normalized area of the posterior leaflet (0.57 ± 0.15 vs. 0.66 ± 0.18; P = .016) compared to healthy dogs of other breeds; this results in CKCSs having a flatter MV with reduced tenting, compared to the MV of other breeds. Conclusions and Clinical Importance: These morphologic features could confer a mechanical disadvantage and play a role in the predisposition of CKCSs to the early development of MMVD.